2021
DOI: 10.1002/jhet.4331
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and bioactivity evaluation of eugenol hybrids obtained by Mannich and 1,3 dipolar cycloaddition reactions

Abstract: Design, synthesis, and bioactivity evaluation of novel mannich bases (2a-2j) and triazole-chalcone derivatives (7a-7k) of Eugenol 1 were reported. Among all the derivatives tested for antiproliferative activity, di-amine manich derivative 2b (32.92 μM), and 4-methoxy chalcone triazole derivative 7d (33.05 μM) significantly inhibited HepG2 cell lines when compared to the standard doxorubicin (37.29 μM). Whereas most of the compounds such as diethylamine 2a (17.75 μM), (aminomethyl) methane diamine 2b (17.02 μM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Phenolic Mannich bases of simple phenols have been also evaluated as anticancer agents. Out of ten Mannich bases of eugenol, compound 55 (NR 2 =N(CH 2 NH 2 ) 2 ) (Figure 8) had a broad antiproliferative activity against A549, HepG2, MCF‐7 and SK‐OV‐3 cell lines used in the study, and was more potent (IC 50 =33 μM) than doxorubicin against HepG cells [69] . Aminomethylation of hydroxychavicol took place at the least…”
Section: Anticancer and Cytotoxic Activity Of Mannich Bases Derived F...mentioning
confidence: 99%
See 1 more Smart Citation
“…Phenolic Mannich bases of simple phenols have been also evaluated as anticancer agents. Out of ten Mannich bases of eugenol, compound 55 (NR 2 =N(CH 2 NH 2 ) 2 ) (Figure 8) had a broad antiproliferative activity against A549, HepG2, MCF‐7 and SK‐OV‐3 cell lines used in the study, and was more potent (IC 50 =33 μM) than doxorubicin against HepG cells [69] . Aminomethylation of hydroxychavicol took place at the least…”
Section: Anticancer and Cytotoxic Activity Of Mannich Bases Derived F...mentioning
confidence: 99%
“…Out of ten Mannich bases of eugenol, compound 55 (NR 2 = N(CH 2 NH 2 ) 2 ) (Figure 8) had a broad antiproliferative activity against A549, HepG2, MCF-7 and SK-OV-3 cell lines used in the study, and was more potent (IC 50 = 33 μM) than doxorubicin against HepG cells. [69] Aminomethylation of hydroxychavicol took place at the least [70] Depending on the nature of the amine reagent, aminomethylation of thymol occurred either ortho or para to the hydroxyl group to give two series of Mannich bases 57 and 58 (Figure 8), whose evaluation against Ca9-22, HSC-2, HSC-3 and HSC-4 human oral squamous carcinoma cell lines showed that they generally had moderate to poor cytotoxicity (CC 50 > 50 μM). [71] Mannich bases 59 (Figure 8) were prepared from structurally diverse phenols as substrates and ciprofloxacin as amine reagent, and their evaluation towards multiple cancer cell lines at National Cancer Institute showed that aminomethylated 1-and 2-naphthols were the most potent in this series against many of the tested cell lines.…”
Section: Chemmedchemmentioning
confidence: 99%
“…No improvement in the antiradical activity of compounds 1, 2 and 4, while eugenol methylpiperazine 3 experienced a decrease in activity compared to eugenol (Table 1). Buduma et al [2] have recently reported the synthesis and antiradical property of compounds 2, 3 and 5. Derivative 3 showed better DPPH scavenging of 64.15 %, at 10 μg/mL, as well as better ABTS scavenging of 98.79 %, at 25 μg/mL.…”
Section: Antiradical Activitymentioning
confidence: 99%
“…When synthetic eugenol derivatives were tested in vitro for their ability to inhibit pancreatic lipase, compound 59) also exhibited moderate antilipase activity. 1 The structures of these compounds are given in Figure 11.…”
Section: Antilipase Activity Of Mannich Basesmentioning
confidence: 99%
“…Mannich bases and their derivatives are being developed with the aim of improving their physicochemical and druglike characteristics, which may have greater influence over pharmacological applications. [1][2][3] Many bioactivities, such as antineoplastic, diuretic, antipsychotic, anticonvulsant, centrally acting muscle relaxant, antibacterial and antiviral ones, are present in https://doi.org/10.18231/j.ijpca.2023.004 2394-2789/© 2023 Innovative Publication, All rights reserved. 15 the Mannich base of heterocyclic compounds.…”
Section: Introductionmentioning
confidence: 99%